Mantle magma-thermofluidodynamic and intracrustal granitoid-hydrothermal-metasomatic auriferous systems; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 1 - Korobeynikov A. F. (Geology and minerals, 2007)
Заглавие с титульного листа